Application of enhanced membrane bioreactor (eMBR) for the reuse of carwash wastewater. (15th January 2020) - Moazzem, Shamima; Ravishankar, Harish; Fan, Linhua; Roddick, Felicity; Jegatheesan, Veeriah
Abstract: Minimising the usage of potable water in industrial and cleaning processes is essential to conserve fresh water. Recycling treated wastewater will help to do so. However, high quality treated wastewater is required for reuse and recycling. This study evaluated the performance of an enhanced membrane bioreactor (eMBR) in treating car wash wastewater for the purpose of reuse. The eMBR consisted of an anaerobic tank, an anoxic tank, an aerobic membrane bioreactor (AMBR) and a UV disinfection unit. The effects of hydraulic retention time of the eMBR on the treated water quality parameters and operating parameters were evaluated. The eMBR produced high quality recyclable water (0.5–10.2 mg/L of COD, 0.18–0.83 NTU of turbidity, 0 org. of E. Coli /100 mL) meeting Class A recycle water standards. Decrease in the mixed liquor suspended solids concentration in the AMBR (from 294 to 117 mg/L) reduced the fouling of the membrane which increased the permeate flux (from 5.9 to 6.7 L/m 2 h). This is unique to the eMBR system used in this study. However, when the flux exceeded the critical flux, the trans-membrane pressure increased significantly. Graphical abstract: Image 1 Highlights: Enhanced MBR (eMBR) produced high quality recycle water from car wash wastewater. Membrane flux was related to MLSS in the aerobic MBR through critical flux tests. The critical flux for continuous mode of operation was 10.3 L/m 2 h. The critical flux for intermittent mode of operation was 7.8 L/m 2 h. The flux and TMP decreased when HRT increased while COD removal remained similar.